2016
DOI: 10.3389/fphar.2016.00114
|View full text |Cite
|
Sign up to set email alerts
|

Phemindole, a Synthetic Di-indole Derivative Maneuvers the Store Operated Calcium Entry (SOCE) to Induce Potent Anti-Carcinogenic Activity in Human Triple Negative Breast Cancer Cells

Abstract: Triple-negative breast cancer (TNBC), is a specific subtype of epithelial breast tumors that are immuno-histochemically negative for the protein expression of the estrogen receptor (ER), the progesterone receptor (PR) and lack over expression/gene amplification of HER2. This subtype of breast cancers is highly metastatic, shows poor prognosis and hence represents an important clinical challenge to researchers worldwide. Thus alternative approaches of drug development for TNBC have gained utmost importance in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…The proteins of pellet (1) were eluted with soft elution buffer (SEB). This step resulted in pellet (2) and supernatant (2). Pellet (2) was subjected to 10% SDS-PAGE and subsequent Western blotting with anti-phosphoserine antibody.…”
Section: Ac8 Prevents Phosphorylation Of Orai1 At Ser-27 and -30mentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins of pellet (1) were eluted with soft elution buffer (SEB). This step resulted in pellet (2) and supernatant (2). Pellet (2) was subjected to 10% SDS-PAGE and subsequent Western blotting with anti-phosphoserine antibody.…”
Section: Ac8 Prevents Phosphorylation Of Orai1 At Ser-27 and -30mentioning
confidence: 99%
“…Consequently, this type of cancer is resistant to hormonal therapies and chemicals that target the HER2 receptor [1]. Studies in TNBC cells revealed that Ca 2+ signaling is remodeled and plays a key functional role [2][3][4][5]. TNBC cells overexpress Orai1, which is responsible for the activation of store-operated Ca 2+ entry (SOCE) [6].…”
Section: Introductionmentioning
confidence: 99%
“…A final collection of 2140 compounds was tested. A triazole (14) from the final screening library was selected as a hit for further elaboration since, although containing both a triazole unit and the dichlorobenzene unit of miconazole, it was overall novel and showed encouraging potency and selectivity for Orai1 in the FLIPR assay. The ability of FLIPR to simultaneously assess Ca2+ levels in 384 wells over the entire experimental period was critical in defining the properties of peak 1 and peak 2 for each tested compound, and would not be possible using approaches not capable to complete simultaneous assessment of all wells (new ref 40).…”
Section: Biologymentioning
confidence: 99%
“…12 Silencing of Orai1 reduces proliferation and metastasis of breast cancer cells such as MDA-MB-231 basal-like breast cancer cells 12,13 and pharmacological inhibition of SOCE has been shown to reduce the proliferation and metastasis of MDA-MB-231 breast cancer cells. 13,14 A variety of agents have been reported 15,16 to inhibit SOCE and this pathway has been highlighted as an opportunity for therapies for the treatment of a variety of diseases. 17 In this study we assessed the effects of a number of reported inhibitors of SOCE in MDA-MB-231 breast cancer cells using a Fluorescence Imaging Plate Reader (FLIPR), and also report on a novel class of triazole-based SOCE inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, under acidic conditions, indole-3-carbinol is dimerised into 3,3′-diindolylmethane (DIM) which exhibited superior activity as apoptosis inducing agent over indole-3-carbinol 2 , 3 . Moreover, Phemindole ( Figure 1 ) overcame the poor bioavailability of DIM and illustrated apoptotic activity against triple negative breast cancer cells (MDA-MB-231) through reactive oxygen species (ROS) mediated mitochondrial-dependent apoptosis 4 . Modifications for both I3C and DIM took place to get more active compounds.…”
Section: Introductionmentioning
confidence: 99%